6 - Coopération Arabo-Burkinabe: Bilan & Perspectives - Talata Kafando (Africa Development, 1986)
Economic and cultural relations between the present Burkinabé State and the Arab World existed long before the colonial era. However due to the present crisis in the international economic relations they have moved into their present stage. An evaluation of public transfers of part of the Arab oil revenue to Burkina shows that these transfers are related to those undertaken by the "Centre" and that they are based on criteria which are not so different, if private Arab investments were to be made, the selection criteria would be those defined in an Islamic Conference project, which are hardly any different from those at the "Center". Cooperation for an autonomous development requires other development strategies with a national and democratic content.